KEMAMPUAN PENALARAN ADAPTIF DITINJAU DARI GAYA BELAJAR DALAM MATERI BARISAN DAN DERET ARITMETIKA - Ana Amah, Dewi Mentari; Jamiah, Yulis; Yani T, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe fact in math education is the student’s adaptive reasoning ability that is still low. Adaptive reasoning ability are influenced by some factors, one of them is student’s learning style. Therefore, adaptive reasoning ability should be analyzed based on student’s learning style. This research aim to describe the adaptive reasoning ability based on learning style in arithmetic sequence and series at SMA Santo Fransiskus Asisi Pontianak. The research method use descriptive method with case study. The subject in this research are eight student’s from all learning style. The result of data analysis showed that the adaptive reasoning ability are different depending on their learning style. Student’s who have diverger learning style can fulfill one indicator of adaptive reasoning ability such as propose hypothesis or conjecture. Student’s who have assimilator learning style can fulfill three indicators of adaptive reasoning ability such as propose hypothesis or conjecture, give reason of the given answer, and make conclusion from a statement. Student’s who have converger learning style can fulfill all indicators of adaptive reasoning ability. Student’s who have accomodator learning style can fulfill one indicator of adaptive reasoning ability such as make conclusion from a statement. Keywords: Adaptive Reasoning Ability, Learning Style, Arithmetic Sequence and                   Series